(untitled) (Swiss Medical Weekly, 2018)
BACKGROUND The introduction of direct acting antivirals (DAAs) for the therapy of chronic hepatitis C (CHC) has revolutionised treatment and marks a paradigm shift in the approach to this disease, rendering interferon-based therapies obsolete. AIMS OF THE STUDY We retrospectively and prospectively evaluated treatment results after the introduction of DAA in Switzerland in a cohort of patients with CHC. METHODS We examined 565 patients who received DAA treatment for CHC between November 2013 and June 2016 with regard to HCV genotype, fibrosis stadium, treatment and outcome. In addition, outcome of re-treatment and resistance-associated substitutions (RAS) in patients that did not achieve sustained virological response (SVR) were evaluated. The majority of patients participate in the Swiss Hepatitis C Cohort Study. Data were evaluated in an intention-to-treat and a modified intention-to-treat analysis. RESULTS Overall SVR rate for all patients was 94% (530 of 565, 95% CI 92–96%). Of 350 patients with HCV genotype 1 CHC, 335 achieved SVR, resulting in an SVR rate of 96% (335 of 350, 95% CI 94–98%). Patients with HCV genotype 2 achieved SVR in 94% (48 of 51, 95% CI 87–100%). Patients with HCV genotype 3 showed SVR of 92% (98 of 107, 95% CI 87–97%). In patients with HCV genotype 4, the SVR rate was substantially lower at 85% (49 of 57, 95% CI 76–94%). The rate of advanced liver fibrosis (Metavir F3/F4) assessed by means of liver biopsy or Fibroscan® in the entire patient population was 71% (404 of 565). Out of 35 patients that did not achieve SVR after DAA treatment, 32 had a relapse and 3 patients showed viral breakthrough. In 17 of 35 cases (49%) patients were treatment naïve and 21 of 35 patients (60%) were cirrhotic. RAS genotyping of HCV was performed in 14 patients. Nine of these 14 patients (60%) carried mutations in the NS5A region of the virus genome. Twenty-seven percent of patients who experienced treatment failure were not treated with recommended regimens as a result of drug availability and reimbursement limitations. CONCLUSION In Switzerland, novel DAA treatments for CHC reflect the positive results from registration trials. Genotypes 2 and 4 remained more difficult to treat between 2014 and 2016. Patients who experienced a relapse after DAA treatment in Switzerland predominantly showed mutations in the NS5A region of the virus genome. DAA treatment limitations in Switzerland did prevent optimal treatment regimens in some patients.